Uma perspectiva para a alfabetização: método fônico - Bachega, Elaine Aparecida Santos (Universidade Federal de São Carlos, 2025)
We know that in Brazil, the topic of literacy is constantly under tension. The media often reports on the low performance of students in assessments that measure the level of education. Part of this is due to the low reading proficiency of our children. The search for an appropriate methodology for teaching literacy has become a controversial and widely discussed subject in the field of education. The phonics method, analyzed in this article, is based on the principle of teaching the sound of letters, showing the relationship between speech sounds (phonemes) and letters (graphemes). This method allows children to develop phonological awareness, enabling them to understand that when letters come together they form syllables, words, sentences and texts. A sequence that goes from the simple to the more complex. Thus, this article analyzed recent studies that show that using the phonics method for the literacy process contributes to and brings positive results for education.
A perspective for literacy: phonics method
Keywords: Alfabetização; Método fônico; Consciência fonológica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM